Sioki, Niki - (:unkn) unknown (My University, 2026)
Niki Sioki is Associate Professor at the University of Nicosia, Cyprus. She holds a PhD in Typography and Graphic Communication from the University of Reading, UK. Her research interests concentrate on design and printing history, with a special focus on Cyprus and Greece, and design and typographic research in postgraduate education. Her most recent publications include the (co)edited book ‘Design for visual communication’ (Cambridge Scholars Publishing 2019) and the research paper ‘The postwar schoolbook as a material artefact. Two Greekreading textbooks from 1944” (Journal of Educational Media, Memory And Society, 11 (1), 2019). She is a member of design professional associations and scholarly societies and regularly serves in conference scientific/organizing committees and editorial boards of academic publications.